Strategic Modelling for High-Technology Sectors: Addressing Economic Security in Emerging Economies amidst US-China Geopolitical Competition (National Security: A Journal of the National Defence University-Kenya, 2025)
This paper presents a quantified strategic model to support emerging economies in enhancing economic security and technological self-reliance in high-technology sectors, using the semiconductor industry as a primary case study. Situated in the context of intensifying US-China geopolitical competition, the study analyses the readiness of India and Kenya to develop resilient semiconductor ecosystems. A mixed-methods approach, combining literature review, stakeholder surveys, and expert validation, informs the development of a weighted scoring model that captures the influence of geopolitical dynamics, domestic capabilities, and regional collaboration on economic outcomes. Findings reveal that, while India demonstrates moderate readiness through policy initiatives such as the Production Linked Incentive (PLI) scheme, significant gaps remain in R&D investment and advanced manufacturing. Kenya, though at an earlier stage, demonstrates potential through digital infrastructure projects like Konza Technopolis, but faces foundational challenges in capacity building and policy alignment. The study further generalises the model to other high-tech sectors such as renewable energy, telecommunications, and artificial intelligence, offering a scalable framework for policymakers. By identifying priority areas and proposing a structured implementation roadmap, this study contributes actionable insights for emerging economies seeking to navigate technological transitions and build resilient, globally competitive high-tech industries.
Keywords: High-Technology Policy, Economic Security, Semiconductor Industry, Geopolitical Competition, Emerging Economic